04.17 TnfΔare/+: a multimorbidity model of spondyloarthropathies. (1st March 2017) - Denis, Maria C; Karagianni, Niki; Consortium, German Mouse Clinic; Fuchs, Helmut; Galius-Durner, Valerie; de Angelis, Martin Hrabě; Ntari, Lydia; Sakkou, Maria; Kollias, George
Abstract : Background: Spondyloarthropathies are a group of joint-related diseases with burden extending to multiple organs. Co-existing conditions have a major impact on the course and outcome of the disease complicating its diagnosis and management. Patients with spondyloarthropathies have two or more comorbidities including inflammatory bowel disease, psoriasis, cardiovascular disease, uveitis, and osteoporosis. In studying these pathologies and for the evaluation of novel therapeutic approaches, it is critical to carefully choose the animal model that closely reflects the complexity of the respective human pathology. We now use the identification of key cellular and molecular drivers. We have now revisited the TNF ΔARE mouse, a well-established model of spondyloarthropathies, to investigate the extent of comorbid pathologies and identify the molecular and cellular pathways underlying pathogenesis in this animal model. Materials and methods: The TNF ΔARE/+ mouse model expresses de-regulated TNF resulting in the spontaneous development of chronic inflammatory joint and intestinal disease that are characteristic of spondyloarthropathies. The translational value of this mouse model has been established over the years through comprehensive studies on the pathogenic role of TNF as well as through the identification of key cellular and molecular drivers. We have now revisited the TNF ΔARE/+ mouse model to uncover previously unidentified co-developing pathologies. To this end, we have carried out a targeted phenotypic screening of TNF ΔARE/+ animals and a broad systematic phenotyping of these mice at the German Mouse Clinic. Results: Targeted phenotyping revealed that TNF ΔARE/+ mice, in addition to arthritis and Crohn's-like IBD, develop aortic valve disease, salivary gland inflammation and inflammation of the periodontium. Systematic phenotyping revealed deviations in the behaviour, neurology, eye morphology and function, nociception, clinical chemistry and allergic responses of these animals along with pathological findings in kidneys and lungs. Some of these pathologies appear to share common TNF-dependent molecular and cellular mechanisms with arthritis and IBD, supporting a common aetiopathogenic axis. Conclusions: This work further highlights the translational value of TNF ΔARE/+ model as it reveals an even higher degree of complexity simulating the RA multisystemic condition that is observed in human patients. This model offers an ideal platform for the study of co-developing pathologies as well as the evaluation of novel therapeutics targeting multiple manifestations of spondyloarthropathies-related comorbidities.